Policies for sustainable economic growth : lessons from the IMF's experience - Williams, Ewart (Institute of International Relations St. AugustineTT, 1997)
Outlines the main lessons that officers in the Fund have learned about what is required for self-sustaining growth and, in the light of these lessons, examines the recent experience of Latin America and the Caribbean.